PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL TERHADAP OBAT TRADISIONAL MINYAK KARO - Siti Fadilah; Maniar Nainggolan; Reh Bungana Beru Perangin-angin (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
Indonesia is a country with abundant biodiversity scattered in various regions, one of which is biodiversity spread in the Karo Regency area which can be used as a traditional medicine "Karo Oil" for disease prevention, healing, health restoration, and health improvement. The problem is the legal protection of traditional medicines according to Intellectual Property Rights based on statutory regulations in the field of Patents, Copyrights, and Geographical Indication Rights and the government's role in the use of traditional medicinal knowledge in the perspective of intellectual property law in Karo Regency. The researcher uses research method used in this research is library research with the type of research used in this research being normative. Normative research is legal research that is carried out by examining literature or secondary data as the basic material for research by searching for regulations and literature related to the problem under study. Based on the results of the research, it can be seen that: Legal protection for traditional medicines according to Intellectual Property Rights is good for obtaining an invention to then seek legal protection, as well as the process of commercializing the invention to make a profit. The government's role in the use of traditional medicinal knowledge in the perspective of intellectual property law in Karo Regency is that the government has a role as a supporting institution and the government will carry out protection by legal or non-legal means.